Sistem Monitoring Private Automatic Branch Exchange dengan Tampilan Personal Computer Berbasis Wirelless - Yuyun Suprapto; Syamsul Maarif; Tot```ok Warsito; Eriyandi Eriyandi (Jurnal Penelitian)
The telephone is a communication tool that can connect someone with others quickly. Communication using the phone has become a primary need for the community, especially in large cities, agencies, to large enterprises. The phone service users in bulk urgently need a alatyang is the development of telephone communication tool known as the PABX (Private Automatic Branch Exchange). In this study the author uses the theory of the resistors, capacitors, diodes LED, optocoupler, Pro wireless XBee, XBee Pro adapter, PABX theory, the theory of the phone, Atmega 16 microcontroller and programming languages. The method used in this research is to study literature, comparative studies of the lecturers, field studies and through experiments in the laboratory. The conclusion of this design are the technicians who worked on the PABX unit can determine the condition of the telephone line clearly and be more efficient in monitoring the telephone line with a distance of affordable, especially if there is damage to phone lines can directly send on display Personal Computer.